Contação de histórias no ensino-aprendizagem de ciências na perspectiva da inclusão - DIAS, Helen do Socorro Rodrigues (Universidade Federal do Pará, 2020)
The following research is about the process of teaching-learning of science through the ludic strategy of storytelling for people with disabilities (PwD), articulated with the concepts of language, regarding a dialogical context in the education field. Having as an object, the analysis of telling and retelling practice of stories in the dialogical teaching-learning of science, that works with the scientific knowledge for the PwD, in the perspective of educational inclusion. Therefore, this research is based on the studies of Bakhtin (2017, 2018 and 2019) under the enunciative-discursive perspective of language, alterity, responsiveness and emotive-volitional tones that are fundamental concepts for this research; Chassot (2002 and 2018) that works with scientific literacy for the context of science teaching and learning; Vygotsky (2012), who argues about important issues related to the development of PwD; Dohme (2011), Rau (2013) and Huizinga (2008) who discusses about the ludic; Zumthor (1997; 2018), Abramovich (2008) and Sisto (2007) discuss about the performance of storytelling and retelling. The methodology was based on action research (Tripp, 2005), having as a participant a teacher from an institution focused on specialized educational services and four students, one with Down Syndrome, two ID students and one with autism, all between the ages of 06 and 09 years old, with stages of selection of the theme and subtheme of the teaching of science, construction of inedited narrative and pedagogical resources, development of activities with students. The results show that the use of storytelling and retelling stories enhances the dialogical interaction among the individuals, favoring the teaching-learning process of PwD sciences.